2016
DOI: 10.1186/s13071-016-1432-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental factors on the emergence, transmission and distribution of Toxoplasma gondii

Abstract: Toxoplasma gondii is an obligate intracellular protozoan that poses a great threat to human health and economic well-being worldwide. The effects of environmental factors such as changing climate and human activities on the ecology of this protozoan are being discovered. Accumulated evidence shows that changes of these environmental factors can exert influence on the occurrence, transmission and distribution of T. gondii. This article reviews studies from different geographical regions with varying climates, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
88
1
22

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 89 publications
3
88
1
22
Order By: Relevance
“…According to the effect of seasons on infection with T. gondii, Autumn was recorded the highest rate of infection with significant difference, the present study consistent with the study (22) in China where they revealed that T. gondii was found in 6 (3.33%) samples collected in Autumn and 1 (0.56%) collected in winter, this indicated that seasons might have important impacts on the presence of T. gondii, likewise (23) recorded rising in infection rate during winter and spring than Autumn and summer and referred to that seasonal variation of T. gondii infection in human are remarkably different than animals, also seasonal variation study on pregnant women in France appeared that the maximal risk of infection between end of summer to end of Autumn (24). this may be related to the availability of favorable conditions for oocysts maturation and sporulation to become infective (25).…”
Section: Discussionmentioning
confidence: 92%
“…According to the effect of seasons on infection with T. gondii, Autumn was recorded the highest rate of infection with significant difference, the present study consistent with the study (22) in China where they revealed that T. gondii was found in 6 (3.33%) samples collected in Autumn and 1 (0.56%) collected in winter, this indicated that seasons might have important impacts on the presence of T. gondii, likewise (23) recorded rising in infection rate during winter and spring than Autumn and summer and referred to that seasonal variation of T. gondii infection in human are remarkably different than animals, also seasonal variation study on pregnant women in France appeared that the maximal risk of infection between end of summer to end of Autumn (24). this may be related to the availability of favorable conditions for oocysts maturation and sporulation to become infective (25).…”
Section: Discussionmentioning
confidence: 92%
“…Toxoplasma gondii is distributed worldwide from tropical to arctic ecosystems, with an extensive host range that includes all avian, marsupial and mammalian taxa, including humans, with multiple modes of transmission and persistence (Dubey, 2010). The epidemiology of T. gondii has been altered by anthropogenic activities such as agricultural development (Shwab et al, 2018), landscape modification (Shapiro et al, 2010), climate change (Yan, Liang, Zheng, & Zhu, 2016) and the introduction and spread of free‐roaming domestic cats ( Felis domesticus ) worldwide (De Wit et al, 2017; Shwab et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The infection in Central and South America has high prevalence probably due to the high levels of contamination of the environment by oocysts [17]. Accumulated evidence shows that changes in these environmental factors can strongly influence the transmission and distribution of T. gondii, such as rapid urbanization and global warming [18].…”
Section: Discussionmentioning
confidence: 99%